PENGGUNAAN JENIS CURING DAN SUHU EKSTRAKSI TERHADAP KARAKTERISTIK GELATIN KULIT SAPI SPLIT - Dwi Wulandari (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2015)
Gelatin is one type of protein extracted from skin collagen tissue, bone or animal ligament. This study aims to determine the physical and chemical properties of bovine leather split gelatin extracted with acid and base with different extraction temperatures. The materials used are bovine leather split as much as 10 kg. The material is divided into six treatments and three replications is TlRl, T1R2, T1R3 (curing in NaOH 3%, extraction temperature of 60° C, 70° C, 80° C) and T2Rl, T2R2, T2 (curing in HCl 3%, extraction temperature 60 ° C, 70 ° C, 80 ° C). Analysis of data using completely randomized design (CRD) factorial pattern when there are differences to be continued test of Duncan Multiple Range Test (DMRT). The results showed that the effect of curing materials and extraction temperature significantly to yield, water content, ash content, protein content, fat content, gel strength, viscosity and pH gelatin. The average yield of the parameters measured were as follows: acid yield of 14.36%, 13.31% base; Acid water content 6.93%, 8.33% base; Acid ash content of 4.29%, 3.29% base; Protein acid content of 61.34% , 59.85% base; Fatty acid content of 2.53%, 1.99% base; gel strength bloom 100.05 acids, bases 103.92 bloom; viscosity acid of 6.59 cp , 6,95 base and acid pH of 5.68, base is 7.3 Bovine leather split can be made of gelatin with an acid or base curing materials